Do Multinational Enterprises push up the Wages of Domestic Firms in the Italian Manufacturing Sector? - Rosanna Pittiglio; Filippo Reganati; Edgardo Sica (FIW - Research Centre International Economics, 2012)
The present paper aims to test the impact of incoming Foreign Direct Investment (FDI) on local wages in the Italian manufacturing sector by using firm level data from 2002 to 2007. Results initially show the lack of wage spillovers at both horizontal and vertical level, meaning that the effects of foreign investment are completely internalized within each firm. However, when the technology gap is taken into account, we find some evidence of a non-linear relationship between gap size and wage spillover. In particular, if the technological gap between local firms and foreign companies is too large, Multinational Enterprises (MNEs) face some difficulty in interacting with domestic suppliers and customers, with the consequence that they act like monads within the host country. We therefore believe that policies favouring the attraction of inward investments, should not be of the one for all' or one for always' type, but must be strongly directed towards the sectoral and local characteristics of the host country.
Keywords: F21; F23; 330; Foreign Direct Investment; Multinational Enterprises; Horizontal Wage Spillovers; Vertical Wage Spillovers; Technological Gap